Demographics and Volatile Social Security Wealth: Political Risks of Benefit Rule Changes in Germany - Christoph Borgmann; Matthias Heidler (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we address the question how the generosity of the benefit rule of the German public pension system has changed during the past three decades and how this development can be explained by demographic changes. Firstly, we illustrate the political risk of benefit rule changes for individuals. We find that depending on the birth year and the considered scenario the relative losses vary between 30 and nearly 60 percent. Secondly, we estimate how demographic developments have triggered these changes in generosity. Our results suggest that future developments of the old-age dependency ratio have an influence on the determination of generosity.
Keywords: 330; social security wealth; demography; political economy; Germany